Community Health Center: Core Data Project, 2001-2002 - Bradford, Judith B. ([Verlag nicht ermittelbar], 2013)
A survey was administered to any patient that presented for services at a health center between 2001 and 2002. Patients were asked to complete a brief survey with questions relating to demographic, relationship status, reason for choosing this health center, mental health status, and abuse history.